1997
DOI: 10.1007/s002280050338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluvastatin therapy on lipids, antioxidants, oxidation of low density lipoproteins and trace metals

Abstract: Fluvastatin therapy had lipid-lowering and antioxidative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…As a secondary analysis, the small number of dyslipidemic participants might contribute to the lack of power of the analysis as the larger decrease in plasma selenium in the statin group did not reach the statistical significance. Previous reports conducted on a short period and on a limited number of patients did not show any effect of statins on plasma selenium variations [38,39]. It can also be hypothesized that the response of plasma selenium to lipid lowering drugs, observed on cross-sectional analysis, reach a plateau and then is up-regulated by the changes in HDL-and LDL-cholesterol concentrations as suggested by the multiple linear regression models.…”
Section: Discussionmentioning
confidence: 85%
“…As a secondary analysis, the small number of dyslipidemic participants might contribute to the lack of power of the analysis as the larger decrease in plasma selenium in the statin group did not reach the statistical significance. Previous reports conducted on a short period and on a limited number of patients did not show any effect of statins on plasma selenium variations [38,39]. It can also be hypothesized that the response of plasma selenium to lipid lowering drugs, observed on cross-sectional analysis, reach a plateau and then is up-regulated by the changes in HDL-and LDL-cholesterol concentrations as suggested by the multiple linear regression models.…”
Section: Discussionmentioning
confidence: 85%
“…39 Fluvastatin has also been studied in a randomized, double-blind, parallel, placebo-controlled trial design, wherein the daily dose of 80 mg did not change the lag time significantly. 48 As in most of the earlier studies, 17,48 -52 oxidation tests were performed on frozen samples after the entire clinical phase had been completed. If some oxidation or conformational changes did occur in LDL, then lovastatin made LDL more vulnerable to minimal oxidation than placebo, because the conditions were the same for all samples and the treatment periods were balanced.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, fluvastatin at a dose of 40 mg/day administered for 8 weeks in 20 patients with hypercholesterolemia caused the similar reduction of conjugated dienes formed during ex vivo oxidation of LDL (Leonhardt et al 1997). Hussein et al (1997) demonstrated that treatment of hypercholesterolemic subjects with fluvastatin (40 mg/day) for 12 or 24 weeks reduced 2.2-azobis, 2-amidinopropane hydrochloride-(AAPH)-induced peroxidation of plasma lipids by 70 and 77%, respectively.…”
Section: Effect Of Statin Treatment On Ldl Oxidizabilitymentioning
confidence: 97%
“…Consistent with the antioxidant effect of statins, an increase in the GSH/GSSG ratio was noted, but it was not statistically significant. Fluvastatin administered at 40 mg/day for 8 weeks had no effect on α-tocopherol and retinol content in LDL isolated form hypercholesterolemic subjects (Leonhardt et al 1997). In another group of patients with hypercholesterolemia and hypertension, the same treatment regimen did not modify plasma reduced GSH (Hussein et al 2002).…”
Section: Statins and Antioxidant Systemmentioning
confidence: 98%